High-performance alkaline aluminum-air battery composite electrolyte and preparation method thereof
By using agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate in aluminum air batteries, the problem of self-corrosion of aluminum anode is solved, the energy density and cycle life of the battery are improved, and the efficient utilization of aluminum anode and stable electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510722306.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-26
AI Technical Summary
Aluminum air batteries have problems with aluminum anode self-corrosion in alkaline electrolytes, resulting in battery capacity loss and slow kinetics of cathode oxygen reduction reactions. The battery system is usually irreversible and one-time design, which limits its recycling ability.
Agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate were used as composite electrolyte additives. Through physical adsorption of agar powder and the chemical coordination of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine with Zn2+, a stable composite protection interface was constructed, which inhibited the self-corrosion of the aluminum anode and optimized the distribution of discharge products.
The energy density and cycle life of aluminum air batteries have been significantly improved, the aluminum anode utilization rate reaches 79.0%, and the self-corrosion rate is reduced, achieving high energy density of 2829.0mWh g-1 and long-life battery performance.
Smart Images

Figure CN120545569A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for preparing a composite electrolyte additive for alkaline aluminum-air batteries. Background Art
[0002] Aluminum-air batteries are high-energy-density chemical power sources that generate electricity through the reaction of aluminum metal and oxygen. They have been gaining attention since the 1960s. Their operating principle uses aluminum as the negative electrode and oxygen in the air as the positive active material. The hydrogen oxidation reaction in the electrolyte releases electrons, generating an electric current. Compared to traditional lithium-ion batteries, aluminum-air batteries offer significant advantages: abundant aluminum resources, low cost, and easy recycling. Their theoretical energy density can reach 8,100 Wh / kg, far exceeding existing commercial batteries, making them particularly suitable for long-term power supply scenarios. Furthermore, their reaction product, aluminum hydroxide, is environmentally friendly, in line with the development trend of green energy.
[0003] However, this technology still faces multiple challenges. The self-corrosion of the aluminum anode in the alkaline electrolyte leads to capacity loss, the slow kinetics of the cathode oxygen reduction reaction require reliance on precious metal catalysts, which drives up costs, and the battery system is usually an irreversible one-time design, which restricts its recycling capacity. Current research focuses on optimization strategies for electrolyte additives. Functional additives (such as surfactants or ionic liquids) can optimize the wettability of the electrolyte, promote ion transport and reduce product deposition. The multi-dimensional coordinated regulation of these additives provides a key technical path for improving the energy density, extending the cycle life and controlling the cost of aluminum-air batteries. Aluminum-air batteries have been piloted in low-power scenarios such as marine monitoring equipment and remote communication base stations, and have been combined with lithium batteries to form a hybrid system as a range-extending solution for electric vehicles. With breakthroughs in materials science and electrochemical engineering, aluminum-air batteries are expected to open up a unique application ecosystem in the field of energy storage. Summary of the Invention
[0004] The purpose of the present invention is to provide a specific preparation method for an alkaline aluminum-air battery electrolyte additive, addressing the problem mentioned in the background art of aluminum anode self-corrosion in alkaline electrolytes leading to battery capacity loss. The present invention provides a specific preparation method for an alkaline aluminum-air battery electrolyte additive, which can effectively inhibit aluminum anode self-corrosion and improve the anode utilization rate and energy density of aluminum-air batteries. The compounded alkaline aluminum-air battery electrolyte additive is low-cost, environmentally friendly, has abundant raw material resources, and is highly safe, meeting the battery requirements for large-scale energy storage.
[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:
[0006] A high-performance alkaline aluminum-air battery composite electrolyte additive comprises agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate. The additive comprises agar powder at a concentration of 1.5 g / L to 3.5 g / L, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine at a concentration of 1 to 9 mM, and zinc acetate at a concentration of 5 to 15 mM.
[0007] Furthermore, in the composite electrolyte, the concentration of the agar powder is 1.5 g / L, the concentration of the S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9 mM, and the concentration of the zinc acetate is 10 mM.
[0008] The present invention also provides a high-performance alkaline aluminum-air battery composite electrolyte, which comprises a supporting electrolyte and the above-mentioned additives, and the rest is water.
[0009] Furthermore, the supporting electrolyte in the electrolyte is NaOH, and its concentration is 4 mol L -1 .
[0010] The present invention also provides a method for preparing an alkaline aluminum-air battery composite electrolyte, which comprises the following steps:
[0011] (1) Prepare 4 mol L -1 Sodium hydroxide solution, cooled to room temperature for later use;
[0012] (2) Add agar powder, mix well with supporting electrolyte in a water bath with magnetic stirring, and cool to room temperature for later use;
[0013] (3) Add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, stir thoroughly until completely dissolved, and set aside;
[0014] (4) Finally, zinc acetate is added and stirred thoroughly until it is completely dissolved to obtain a composite electrolyte containing additives.
[0015] Furthermore, in step (2), after adding agar powder to the supporting electrolyte sodium hydroxide, the mixture is heated in an 80° C. water bath and magnetically stirred at 200 rpm for 1 hour, and the final concentration of agar powder in the mixed solution is 1.5 g / L-3.5 g / L.
[0016] Furthermore, in the step (3), the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 1-9 mM, and the stirring time is 5 min.
[0017] Furthermore, in step (4), the concentration of zinc acetate is 5-15 mM, and the stirring time is 5 min.
[0018] The present invention also provides a high-performance alkaline aluminum-air battery, which uses the above-mentioned composite electrolyte, including supporting electrolyte sodium hydroxide and a compound additive consisting of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. This invention innovatively discovered that agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate exhibit a synergistic effect as electrolyte additives. Agar powder, rich in hydroxyl (-OH) polar groups, preferentially adsorbs on the aluminum anode surface, effectively covering HER sites and reshaping the electric field distribution at the aluminum anode interface.
[0021] 2. The polar groups (-OH, -COOH) of agar powder in the additive can be preferentially adsorbed on the metal surface, which is the source of cysteine and Zn 2+ It provides an ordered interface environment and promotes the uniform growth of the composite protective layer. The -COOH contained in S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine can stabilize the aluminum / electrolyte interface, and the other group -NH2 contained in it forms a coordination bond with zinc ions, thereby enhancing the adhesion of the zinc deposit layer to the aluminum anode. In general, agar constructs a stable composite protective interface through physical adsorption, chemical coordination of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine with Zn / Al products, and the synergistic effect of electrochemical deposition (zinc acetate), significantly inhibiting the self-corrosion and hydrogen evolution of the aluminum anode, while optimizing the distribution of discharge products, thereby achieving a high energy density of aluminum-air batteries (2829.0mWh g -1 ) and long life.
[0022] 3. The addition of zinc acetate can stabilize the interface layer, enhance the structural integrity of the hydrophobic layer, and further reduce the corrosion of the aluminum anode by the alkaline electrolyte. The composite electrolyte can not only significantly reduce the hydrogen evolution self-corrosion rate of the aluminum anode, but also improve the electrochemical performance of the aluminum-air battery and increase the anode utilization rate, which is as high as 79.0%.
[0023] 4. The optimal composite concentration of the additive proposed by the present invention is that the concentration of agar powder is 1.5g / L, the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9mM, and the concentration of zinc acetate is 10mM.
[0024] First, when the agar powder concentration is too high, the corrosion inhibition efficiency will decrease. This is because excessive agar powder will form a competitive adsorption phenomenon, which causes the HER sites that have been adsorbed and covered to be exposed again, which in turn increases the corrosion efficiency of aluminum. Therefore, controlling the concentration of agar powder helps to improve the corrosion inhibition efficiency of aluminum anodes.
[0025] The synergistic effect of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and agar powder was then tested under controlled agar powder concentration conditions. When the S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine concentration reached a certain level, electrochemical test results showed that the improvement in corrosion inhibition efficiency for the aluminum anode was no longer significant.
[0026] Finally, after determining the effective synergistic concentration of agar powder and S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, zinc acetate was introduced to enhance the interfacial stability of the synergistic reaction between agar powder and S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine on the aluminum anode surface, as well as the structural integrity of the protective layer.
[0027] In general, the composite electrolyte and its additives proposed in the present invention have simple components, low cost, safety, and meet environmental protection requirements, and avoid the use of rare heavy metal ions and harmful substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a graph showing the open circuit voltage (OCP) test of the 5052-grade aluminum alloy in Example 1 of the present invention in a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate.
[0029] Figure 2 This is a polarization (Tafel) curve test diagram of the 5052 grade aluminum alloy in Example 1 of the present invention in a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0030] Figure 3 This is an electrochemical impedance spectroscopy (EIS) test graph of the 5052-grade aluminum alloy in Example 1 of the present invention in a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate.
[0031] Figure 4 This is an LSV test graph of the homemade alkaline aluminum-air battery in Example 2 of the present invention, in which the electrolyte is a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0032] Figure 5 In the self-made alkaline aluminum-air battery of Example 2 of the present invention, the electrolyte is a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate at a flow rate of 20 mA cm -2 Constant current discharge test diagram.
[0033] Figure 6This is an intermittent discharge test diagram of the homemade alkaline aluminum-air battery in Example 2 of the present invention, where the electrolyte is a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0034] Figure 7 This is a step discharge test diagram of the homemade alkaline aluminum-air battery in Example 2 of the present invention, where the electrolyte is a sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0035] Figure 8 This is a graph showing the hydrogen evolution volume results using sodium hydroxide solutions containing agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate at different concentrations in Example 3 of the present invention.
[0036] Figure 9 The present invention is a graph showing the hydrogen evolution rate and the inhibition rate of hydrogen evolution using sodium hydroxide solutions containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate in Example 3.
[0037] Figure 10 For alkaline aluminum-air batteries at 20 mA cm -2 Comparison of various battery performances with and without composite additive electrolytes at different current densities. DETAILED DESCRIPTION
[0038] The present invention is described in detail below with reference to specific examples. This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the scope of protection of the present invention is not limited to the following examples. Unless otherwise specified, the equipment used in the following embodiments is conventional equipment in the art; unless otherwise specified, the reagents used are commercially available products or prepared by conventional methods in the art. All those not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0039] Electrochemical experiments were performed using a three-electrode system, with a platinum electrode as the auxiliary electrode and a Hg / HgO electrode as the reference electrode. The working electrode was sealed with epoxy resin, leaving 1 cm exposed. 2 The working surface was then sanded (400-2000 mesh), ultrasonically degreased with alcohol, rinsed with deionized water, and air-dried. Electrochemical testing was performed on a Chenhua 760E test system.
[0040] Example 1: Three-electrode test
[0041] This embodiment uses a three-electrode test, mainly testing open circuit voltage (OCP), electrochemical impedance spectroscopy (EIS) and polarization curve (Tafel) test. The OCP test time is 1800s; the frequency of the EIS spectrum test is 1-10 5 Hz, the impedance measurement signal amplitude was a 5 mV sine wave; the Tafel curve scan rate was 1 mV / min, and the scan range was ±300 mV relative to the open circuit potential.
[0042] A composite electrolyte for an alkaline aluminum-air battery, comprising 4M sodium hydroxide and additives. The additives include agar powder (A), S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine (S), and zinc acetate (Zn). In the composite electrolyte, the concentration of agar powder is 1.5 g / L, the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9 mM, and the concentrations of zinc acetate are 5 mM, 10 mM, and 15 mM.
[0043] A method for preparing an alkaline aluminum-air battery composite electrolyte comprises the following steps:
[0044] (1) Prepare 200 mL of 4 M sodium hydroxide aqueous solution, cool to room temperature, and record it as sample 1. Repeat the preparation of multiple samples 1 for later use.
[0045] (2) Prepare another portion of sample 1 and add agar powder to make the concentration reach 1.5 g / L. Heat in a water bath at 80°C and stir magnetically at 200 rpm for 1 h. Cool to room temperature. This is recorded as A1.
[0046] (3) Prepare another portion of sample 1 and add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine to a concentration of 9 mM. Stir for 5 minutes until completely dissolved. This is recorded as S9.
[0047] (4) Prepare another portion of sample 1 and add agar powder to a concentration of 1.5 g / L. Heat in an 80°C water bath and stir magnetically at 200 rpm for 1 h. After cooling to room temperature, add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine to a concentration of 9 mM. Stir for 5 min until completely dissolved. This is recorded as A1S9.
[0048] (5) Three samples of sample 1 were prepared and then agar powder was added to make the concentration reach 1.5 g / L (A1). The samples were heated in a water bath at 80 °C and magnetically stirred at 200 rpm for 1 h. After cooling to room temperature, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine was added to make the concentration reach 9 mM (S9). Zinc acetate was then added to make the concentration reach 5 mM (Z5), 10 mM (Z 10 ), 15mM
[0049] (Z 15), stirred for 5 min to completely dissolve, and recorded as A1S9Z5, A1S9Z 10 and A1S9Z 15 .
[0050] A method for preparing an alkaline electrolyte for an aluminum-air battery is as follows:
[0051] (1) Prepare 200 mL of a 4 M sodium hydroxide aqueous solution, cool to room temperature, and record it as Blank.
[0052] An electrochemical experiment of an alkaline aluminum-air battery electrolyte comprises the following steps:
[0053] The pretreated 5052 grade aluminum alloy electrode was placed in the prepared electrolyte and the open circuit potential was first tested for 1800s to stabilize the potential of the electrode. Then, Tafel curve test and EIS test were performed.
[0054] Corrosion inhibition efficiency (η i %) is calculated according to the following formula:
[0055]
[0056] Among them, i corr and i corr(inh) The corrosion current density of 5052 grade aluminum alloy without and with composite additives are shown respectively.
[0057] The fitting parameters of the polarization curves of the aluminum electrode in sodium hydroxide solutions containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate are shown in Table 1.
[0058] Table 1 Tafel curve fitting parameters of 5052 grade aluminum alloy in sodium hydroxide solution containing different concentrations of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate additives
[0059]
[0060]
[0061] As shown in Table 1, additives A1, S9, A1S9, S9Z 10 and A1Z 10 The corrosion inhibition efficiency is much lower than that of composite additives A1S9Z5 and A1S9Z 10, the corrosion inhibition efficiency of A1S9Z15 on aluminum electrodes, and the corrosion inhibition rate of the composite additive on aluminum electrodes increases with the increase of zinc acetate concentration. When the zinc acetate concentration is 10mM, the corrosion inhibition rate is the largest, and the optimal corrosion inhibition rate is 62.6%. Therefore, the present invention prefers zinc acetate to be 10mM, and the composite additive at this concentration has the best corrosion inhibition effect on aluminum.
[0062] Furthermore, it was confirmed that the additives 1.5 g / L agar powder, 9 mM S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and 10 mM zinc acetate contained in the composite electrolyte had the best concentration ratio for corrosion inhibition effect.
[0063] like Figure 1 As shown in the figure, the open circuit potential value of the aluminum electrode in the electrolyte containing the composite additive is 10 The maximum open circuit voltage value in the electrolyte with composite additives is 1.481V.
[0064] like Figure 2 As shown in the figure, the cathode and anodic corrosion current densities of the aluminum electrode in the electrolyte containing the composite additive decreased, and the potential shifted negatively. This indicates that the additive compound of agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate is a mixed corrosion inhibitor. The composite additive primarily reduces the self-corrosion hydrogen evolution reaction of aluminum by adsorbing on the active sites of the aluminum electrode. At the same time, Zn deposition on the aluminum surface also increases the interfacial stability between the aluminum anode and the electrolyte, further enhancing the structural integrity of the protective layer.
[0065] like Figure 3 As shown in the figure, the capacitive reactance arc of the aluminum electrode in the blank solution is the smallest. After adding different concentrations of the composite additive, the capacitive reactance arc of the aluminum electrode becomes larger, which proves that the composite additive can effectively inhibit the corrosion reaction. Among them, when the concentration of agar powder is 1.5g / L, the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9mM, and the concentration of zinc acetate is 10mM, the capacitive reactance arc of the aluminum electrode is the largest. It can be seen that the protective effect of the composite additive is best at this concentration. Therefore, the present invention preferably has a concentration of 1.5g / L agar powder, a concentration of 9mM S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and a concentration of 10mM zinc acetate.
[0066] Example 2: Assembling aluminum-air battery test
[0067] An additive for an alkaline aluminum-air battery composite electrolyte comprises agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate. In the composite electrolyte, the concentration of agar powder is 1.5 g / L, the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9 mM, and the concentration of zinc acetate is 10 mM.
[0068] A composite electrolyte for an alkaline aluminum-air battery comprises sodium hydroxide, agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, and zinc acetate, wherein the concentration of the sodium hydroxide is 4M, the concentration of the agar powder is 1.5 g / L, the concentration of the S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9 mM, and the concentration of the zinc acetate is 10 mM.
[0069] An alkaline electrolyte comprises sodium hydroxide, wherein the concentration of the sodium hydroxide is 4M.
[0070] A method for preparing an alkaline aluminum-air battery composite electrolyte comprises the following steps:
[0071] (1) Prepare sample 1 according to Example 1;
[0072] (2) Prepare another portion of sample 1 and add agar powder to a concentration of 1.5 g / L. Heat at 80°C with magnetic stirring for 1 hour. Cool, then add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine at a concentration of 9 mM and zinc acetate at a concentration of 10 mM. Mix by hand. This is denoted as A1S9Z. 10 .
[0073] A method for preparing an alkaline electrolyte is as follows:
[0074] (1) Prepare 200 mL of a 4 M sodium hydroxide aqueous solution, cool to room temperature, and record it as Blank.
[0075] A performance test of an alkaline aluminum-air battery containing the composite electrolyte comprises the following steps:
[0076] The pre-treated 5052 grade aluminum alloy anode was tested using an electrochemical workstation. In this embodiment, the electrolytes Blank and A1S9Z were prepared. 10 The LSV polarization in the test voltage range is 0V-2V (vs. Hg / HgO). This test reflects the power density and polarization curve of the aluminum-air battery.
[0077] like Figure 4 As shown in the figure, the aluminum-air battery with the composite additive electrolyte has a lower polarizability and higher power density. The overall power density of the aluminum-air battery containing the composite electrolyte is 53.7 mW cm -2 This is significantly higher than the 40.2 mW cm without composite electrolyte. -2 .
[0078] The pre-treated 5052 grade aluminum alloy anode was tested using an electrochemical workstation. In this embodiment, the electrolytes Blank and A1S9Z were prepared. 10 The constant current discharge at 20 mA cm-2 The test was conducted at a constant current density for 1 hour. The mass difference of the aluminum block before and after discharge was calculated to reflect the battery capacity density.
[0079] like Figure 5 As shown, the aluminum-air battery tested with the composite additive electrolyte has a high -2 The capacity density is 2353.6 mAh g -1 , is an electrolyte without composite additives (1169.9mAh g -1 ) test. The energy density also increased from 1319.7mWh g -1 Increased to 2829.0mWh g -1 The anode utilization rate of aluminum-air batteries tested using composite additive electrolytes is as high as 79.0%.
[0080] The capacity density is calculated as follows:
[0081]
[0082] Where Q is the capacity density (mAh g -1 ), I is the current density (mA cm -2 ), t is the time (h), and Δm is the mass difference of the aluminum anode before and after the constant current test (g).
[0083] The energy density is calculated as follows:
[0084]
[0085] Where W is the energy density (mWh g -1 ), E is the average discharge voltage (V), I is the current density (mA cm -2 ), t is the time (h), and Δm is the mass difference of the aluminum anode before and after the constant current test (g).
[0086] The anode utilization rate is calculated according to the following formula:
[0087]
[0088] Where Ua is the anode utilization rate (%), I is the discharge current density (A), t is the discharge time (s), Δm is the mass difference of the aluminum anode before and after the constant current test (g), F is the Faraday constant (96485C·mol -1 ).
[0089] The pre-treated 5052 grade aluminum alloy anode was tested using an electrochemical workstation. In this embodiment, the electrolytes Blank and A1S9Z were prepared. 10In the intermittent discharge, the voltage of the aluminum-air battery is first tested under 20mA constant current discharge for 60 minutes, and then the open circuit voltage is tested for 20 minutes. The above is one cycle. After the aluminum-air battery cycle test, it can be seen whether the discharge performance of the aluminum-air battery is stable.
[0090] like Figure 6 As shown in the figure, the aluminum-air battery tested with the composite additive electrolyte has higher voltage at 20mA and open circuit voltage than the one without the composite additive electrolyte, indicating that the aluminum-air battery containing the composite additive electrolyte has better and more stable discharge performance.
[0091] The pretreated 5052 grade aluminum alloy anode was tested using an electrochemical workstation. In this example, the electrolytes Blank and A1S9Z were prepared. 10 The overall performance of the aluminum-air battery is judged by testing the voltage stability at different currents of 1mA, 10mA, 20mA, 40mA, 60mA, 80mA, 100mA and 120mA in the step discharge. Each current test lasts for 600s. This test can show whether the aluminum-air battery can discharge stably under large current discharge.
[0092] like Figure 7 As shown, at 1-80 mA cm -2 At a circuit density of 100 mA cm, the voltage of the electrolyte containing the composite additive is significantly higher than that of the aluminum-air battery without the composite additive electrolyte. -2 and 120mA cm -2 At higher current density, the discharge voltage of the aluminum-air battery containing the composite electrolyte shows an unstable trend. This is because the higher current density will affect the adsorption of the composite additive on the aluminum surface, thereby reducing the discharge performance of the aluminum-air battery.
[0093] Example 3: Hydrogen evolution test
[0094] An alkaline aluminum-air battery composite electrolyte comprises sodium hydroxide, agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate.
[0095] A method for preparing an alkaline aluminum-air battery composite electrolyte comprises the following steps:
[0096] (1) preparing alkaline electrolyte sample 1 according to the method in embodiment 1;
[0097] (2) Prepare three more samples of sample 1 and add agar powder to a concentration of 1.5 g / L. Heat at 80°C with magnetic stirring for 1 hour. Cool, then add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine at a concentration of 9 mM and zinc acetate at concentrations of 5 mM, 10 mM, and 15 mM. Mix by hand. Note: A1S9Z 10 、A1S9Z 10 and A1S9Z 15 ;
[0098] A method for preparing an alkaline electrolyte is as follows:
[0099] (1) Prepare 200 mL of a 4 M sodium hydroxide aqueous solution, cool to room temperature, and record it as Blank.
[0100] The reaction area is 1 cm 2 A 5052 grade aluminum block was placed in a constant temperature electrolyte at 25°C, and the H2 generated by the self-corrosion of the aluminum block was recorded every 5 minutes using the drainage gas collection method for a total of 30 minutes.
[0101] like Figure 8 The blank electrolyte and the electrolyte containing composite additives (A1S9Z 10 、A1S9Z 10 and A1S9Z 15 ) The volume of H2 released is recorded. Obviously, the electrolyte A1S9Z 10 In the same time, it has a lower H2 precipitation volume. Figure 9 As shown, the hydrogen evolution rate of Blank electrolyte is 0.58 mL cm -2 min -1 , while the electrolyte containing composite additives is significantly lower, and the lowest hydrogen evolution inhibition efficiency is the electrolyte containing A1S9Z 10 The electrolyte is 0.22 mL cm -2 min -1 The corresponding hydrogen evolution inhibition efficiency is as high as 62.1%.
[0102] Hydrogen evolution rate ( ) is calculated as follows:
[0103]
[0104] in, is the volume of hydrogen evolution (mL), A is the reaction area (cm 2 ), T is hydrogen evolution time (min);
[0105] Inhibition of hydrogen evolution efficiency ( ) is calculated as follows:
[0106]
[0107] Where R0 is the hydrogen evolution rate of Blank electrolyte, R inh is the hydrogen evolution rate of the electrolyte containing the composite additive.
[0108] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.
Claims
1. A high-performance additive for alkaline aluminum-air battery composite electrolyte, characterized in that: The additives of the alkaline aluminum-air battery composite electrolyte include agar powder, S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine and zinc acetate, the concentration of the agar powder is 1.5g / L-3.5g / L, the concentration of the S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 1-9mM, and the concentration of the zinc acetate is 5-15mM.
2. The additive according to claim 1, characterized in that In the electrolyte, the concentration of agar powder is 1.5 g / L, the concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine is 9 mM, and the concentration of zinc acetate is 10 mM.
3. A high-performance alkaline aluminum-air battery composite electrolyte, characterized in that: The composite electrolyte comprises a supporting electrolyte and the additive according to any one of claims 1 to 2, and the remainder is water.
4. A high performance alkaline aluminum-air battery composite electrolyte according to claim 3, characterized in that: The supporting electrolyte in the electrolyte is NaOH, with a concentration of 4 mol L -1 .
5. A method for preparing a high-performance alkaline aluminum-air battery composite electrolyte according to any one of claims 3 to 4, characterized in that: The following steps are included: (1) Prepare supporting electrolyte sodium hydroxide solution and cool to room temperature for later use; (2) Add agar powder, mix well with supporting electrolyte in a water bath with magnetic stirring, and cool to room temperature for later use; (3) Add S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine, stir thoroughly until completely dissolved, and set aside; (4) Finally, zinc acetate is added and stirred thoroughly until it is completely dissolved to obtain a composite electrolyte containing additives.
6. The method for preparing a high-performance alkaline aluminum-air battery composite electrolyte according to claim 5, characterized in that: In the step (2), after adding agar powder to the supporting electrolyte sodium hydroxide, the mixture is heated in an 80° C. water bath and magnetically stirred at 200 rpm for 1 hour, and the final concentration of agar powder in the mixed solution is 1.5 g / L.
7. The method for preparing a high-performance alkaline aluminum-air battery composite electrolyte according to claim 5, characterized in that: The concentration of S-acetylmethyl-N-tert-butylcarbonyl-L-cysteine in step (3) is 9 mM.
8. The method for preparing a high-performance alkaline aluminum-air battery composite electrolyte according to claim 5, characterized in that: The concentration of zinc acetate in step (4) is 5mM-15mM.
9. A high performance alkaline aluminum-air battery, characterized in that: The alkaline battery adopts the composite electrolyte described in claim 4.